Levodopa Modulates Functional Connectivity in the Upper Beta Band Between Subthalamic Nucleus and Muscle Activity in Tonic and Phasic Motor Activity Patterns in Parkinson’s Disease - Ramirez Pasos, Uri E.; Steigerwald, Frank; Reich, Martin M.; Matthies, Cordula; Volkmann, Jens; Reese, René (Frontiers in Human Neuroscience, 2019)
Introduction: Striatal dopamine depletion disrupts basal ganglia function and causes Parkinson´s disease (PD). The pathophysiology of the dopamine-dependent relationship between basal ganglia signalling and motor control, however, is not fully understood. We obtained simultaneous recordings of local field potentials (LFP) from the subthalamic nucleus (STN) and electromyograms (EMG) in patients with PD to investigate the impact of dopaminergic state and movement on long-range beta functional connectivity between basal ganglia and lower motor neurons. Methods: 8 PD patients were investigated three months after implantation of a DBS-system capable of recording LFPs via chronically-implanted leads (Medtronic, ACTIVA PC + S®). We analysed STN spectral power and its coherence with EMG in the context of two different movement paradigms (tonic wrist extension versus alternating wrist extension and flexion) and the effect of L-Dopa intake using an unbiased data-driven approach to determine regions of interest (ROI). Results Two ROIs capturing prominent coherence within a grand average coherogram were identified. A trend of a dopamine effect was observed for the first ROI (50–150 ms after movement start) with higher STN-EMG coherence in medicated patients. Concerning the second ROI (300–500 ms after movement start), an interaction effect of L-Dopa medication and movement task was observed with higher coherence in the isometric contraction task compared to alternating movements in the medication ON state, a pattern which was reversed in L-Dopa OFF. Discussion: L-Dopa medication may normalize functional connectivity between remote structures of the motor system with increased upper beta coherence reflecting a physiological restriction of the amount of information conveyed between remote structures. This may be necessary to maintain simple movements like isometric contraction. Our study adds dynamic properties to the complex interplay between STN spectral beta power and the nucleus’ functional connectivity to remote structures of the motor system as a function of movement and dopaminergic state. This may help to identify markers of neuronal activity relevant for more individualised programming of DBS therapy.